BOYLE GAY LUSSAC EKSPERIMENT USING AIR AS A TEACHING AID SENIOR HIGH SCHOOL (SMA/MA) - ROHMANAH (NIM 20206018), SITI
The law of Boyle-Gay Lussac is one of main physic topics which is interesting to learn and examined. This law is about a state of matters called gas. State of gas in a closed cylinder can be determined by pressure (p), volume (V), and temperature (T). These quantities are usually called state variable. Change of this quantities in a process in constant temperature is called isothermal process, at constant pressure is called isobaric process, and at contant volume is called isochoric process. Graphs yielded from isothermal, isobaric, and isochoric processes have been used to help the understanding of Boyle-Gay Lussac law. This final project is about designing a theaching aid which is a simple using air at ideal gas to show Boyle-Gay Lussac law. Isothermal process has been reached at about 313 K (R2=0,998), in about 775 mmHg isobaric process could be shown (R2=0,999), and in about 1015 ml (R2=1) isochoric process could be observed. The difference between data yielded in this experiment with would of ideal gas law is 0-0,00998%. According some referefes such values show that this equipment is good enough to be used as teaching aid in SMA/MA.